KORELASI KEBIJAKAN HARGA BERAS DENGAN KESEJAHTERAAN PETANI DI PROVINSI SULAWESI TENGGARA - Vibriane, Erra Septy; Saenong, Zainuddin; Ernawati, Ernawati (Pascasarjana Universitas Halu Oleo, 2017)
The objectives of this research are: (1) to know the relationship between Government Purchase Price (HPP) policy with the Rice Price at farmer level in Sulawesi Tenggara Province and (2) to know the correlation between Government Purchase Price (HPP) policy with farmers welfare in Sulawesi Tenggara Province. This research usemonthly data in the form of data of HPP of Rice, Grain Price, and Farmer’s Term of Trade of Food Crops Sub-sector (NTP-TP). The Correlation between HPP of Rice andGrain Price and also HPP of Riceand NTP-TP done separately by using Pearson Correlation Analysis. Results of this study showed that there is a direct and significant correlation between rice price policy and price of grain but this price policy even decreased the welfare of foodcrop farmers in Sulawesi Tenggara Province. This is because the price policy is only able to stimulate agricultural production but not followed by neither the control of the rate of increase in household consumption nor production cost. Keywords: Price Policy, Rice Policy, Farmers Welfare